Complete mitochondrial genome of Scincella modesta (Squamata: Scincidae) and phylogenetic analysis - Jun Zhong; Li Ma; Kun Guo; Yu Du (Mitochondrial DNA. Part B. Resources, 2020)
We sequenced and annotated the complete mitochondrial genome (mitogenome) of Scincella modesta (Squamata: Scincidae). This mitogenome was 17,466 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes, 2 ribosomal RNA genes, and 2 non-coding regions. The overall nucleotide composition was 31.8% of A, 14.5% of G, 27.2% of T, and 26.5% of C. Phylogenetic analysis using Bayesian Inference (BI) validated the taxonomic status of S. modesta, exhibiting the close relationship with the other two species from the genus Scincella.